Clinical profile and immediate outcome of children admitted with foreign body aspiration: experience at Dr. Vaishampayan Memorial Government Medical College, Solapur, Maharashtra - Ghodke, Sujit B.; D., Manasa; Bhori, Neelofar; Savaskar, Shakira V.; Takalkar, Anant A. (International Journal of Contemporary Pediatrics, 2022)
Background: Foreign body (FB) aspiration is an uncommon but potentially life-threatening situation that requires urgent intervention. It occurs more commonly among children than in adults. The clinical presentation varies depending on the location of FB in the airway. Patients may be asymptomatic, but when present, symptoms range from acute onset of cough, shortness of breath and at times, asphyxiation. Objective of the research was to study the clinical pattern and immediate outcome of children admitted with foreign body aspiration (FBA). Methods: Descriptive observational study was carried out at department of paediatrics at Dr. VMGMC Solapur during the study period of September 2019 to October 2021. Statistical analysis was done using statistical package for the social sciences (SPSS) 24.0 version. Results: Mean age of the study population was 4.16±2.74 years. Males were 26 (52%) and females were 24 (48%) in our study. Males were predominant in our study with male to female ratio as 1.08:1. Groundnut was commonest FB seen in 34%. Commonest location of FB was right nose in 18 (36%), left nose in 12 (24%). Commonly seen symptoms were irritability in 58%, fever in 40%, vomiting in 40% and cough in 38%. Mortality rate was 2% in our study. Conclusions: Commonly observed aspiration of suspected FB was groundnut in 34% and chana in 20% cases. Most common symptom after aspiration revealed that the irritability in 29 (58%), fever 20 (40%) and vomiting in 20 (40%) cases. Mortality rate was 2% in our study.